Resilience Dynamics of Urban Water Supply Security and Potential of Tipping Points. Issue 10 (24th October 2019) - Krueger, E. H.; Borchardt, D.; Jawitz, J. W.; Klammler, H.; Yang, S.; Zischg, J.; Rao, P. S. C.
Abstract: Cities are the drivers of socioeconomic innovation and are also forced to address the accelerating risk of failure in providing essential services such as water supply today and in the future. Here, we investigate the resilience of urban water supply security, which is defined in terms of the services that citizens receive. The resilience of services is determined by the availability and robustness of critical system elements or "capitals" (water resources, infrastructure, finances, management efficacy, and community adaptation). We translate quantitative information about this portfolio of capitals from seven contrasting cities on four continents into parameters of a coupled system dynamics model. Water services are disrupted by recurring stochastic shocks, and we simulate the dynamics of impact and recovery cycles. Resilience emerges under various constraints, expressed in terms of each city's capital portfolio. Systematic assessment of the parameter space produces the urban water resilience landscape, and we determine the position of each city along a continuous gradient from water insecure and nonresilient to secure and resilient systems. In several cities stochastic disturbance regimes challenge steady‐state conditions and drive system collapse. While water insecure and nonresilient cities risk being pushed into a poverty trap, cities which have developed excess capitals risk being trapped in rigidity and crossing a tipping point from high to low services and collapse. Where public services are insufficient, community adaptation improves water security and resilience to varying degrees. Our results highlight the need for resilience thinking in the governance of urban water systems under global change pressures. Plain Language Summary: We evaluated the resilience of global urban water supply systems, including in economically advanced cities and those characterized by a prevalence of informal settlements lacking basic infrastructure services. Global change challenges urban resilience with more frequent floods, droughts, population growth, and competition for resources. We demonstrate that urban resilience requires the availability of financial and other "capitals" (water, infrastructure, and efficient governance institutions) as well as robust responses to extreme events. Application of a system dynamics model shows the impact of and recovery from repeated shocks for each city, and that tipping points may be crossed, if changing conditions are not adequately addressed. When public water supply services fail, citizens adapt by buying water from private vendors or storing water in rooftop tanks. However, inequality in adaptive capacity exists within and across cities and leaves citizens in precarious situations. Repeated shocks impair development potential, and cities risk getting caught in a poverty trap. Focus on the development of capitals but neglect of robustness can push cities into a "rigidity trap" characterized by degrading services. Finally, predictions of the timing and magnitude of extreme events will remain unreliable, and managing for resilience will require managers to embrace probabilistic scenarios and uncertain futures. Key Points: Analyses using data‐model synthesis of seven global cities reveal coevolution of security and resilience in urban water supply systems Global and climate change with increasing, unpredictable shocks can push urban water systems across tipping points Resilience emerging from community adaptation is highly variable across and within cities, leading to high inequality and precariousness